Intelligent Information and Database Systems: 7th Asian Conference, ACIIDS 2015, Bali, Indonesia, March 23-25, 2015, Proceedings, Part I - Nguyen, Ngoc Thanh; Trawiski, Bogdan; Kosala, Raymond (Lecture Notes in Computer Science, 2015)
The two-volume proceedings of the ACIIDS 2015 conference, LNAI 9011 + 9012, constitutes the refereed proceedings of the 7th Asian Conference on Intelligent Information and Database Systems, held in Bali, Indonesia, in March 2015.